2016
DOI: 10.1111/cpr.12231
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone modulates endothelial progenitor cell (EPC) viability through theCXCL12/CXCR4/PI3K/Akt signalling pathway

Abstract: The CXCL12/CXCR4/PI3K/pAkt signalling pathway increased progesterone-induced EPC viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…This decrease in the quantity of EPCs may be attributed to the steroid-induced decrease in nitric oxide activity leading to EPC senescence and apoptosis [43,44]. In the process of vascular repair, recent studies have shown that SDF-1α-mediated signaling pathways play important roles in enhancing EPC mobilization and functions in ischemic disease models [23,24,45]. In our study, systematic and local changes in the expression of SDF-1α and the quantitative variations of EPCs in rat peripheral blood potentially revealed the mechanism of miR-137-3p silencing in promoting micro-vessel repair in SONFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in the quantity of EPCs may be attributed to the steroid-induced decrease in nitric oxide activity leading to EPC senescence and apoptosis [43,44]. In the process of vascular repair, recent studies have shown that SDF-1α-mediated signaling pathways play important roles in enhancing EPC mobilization and functions in ischemic disease models [23,24,45]. In our study, systematic and local changes in the expression of SDF-1α and the quantitative variations of EPCs in rat peripheral blood potentially revealed the mechanism of miR-137-3p silencing in promoting micro-vessel repair in SONFH.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that stromal cell-derived factor-1α (SDF-1α) is the product of CXCL12. Activation of the SDF-1α/C-X-C chemokine receptor 4 (CXCR4) axis has been implicated in the process of angiogenesis, including recruitment of endothelial progenitor cells (EPCs) [23,24] and endothelial cell migration [25]. EPCs are a type of bone marrow-derived premature progenitor cells [26], which are characterized as CD45 low /CD34 + /VEGFR2 + [27].…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones (eg, estrogen and progesterone) are able to up‐regulate the mRNA and protein expression of CXCR4 in human ESCs for implantation and pregnancy . In addition, the CXCL12/CXCR4 signaling pathway enhances progesterone‐induced endothelial progenitor cell viability . The above evidences suggest that CXCL12/CXCR4 axis plays an important role in embryonic development during the early pregnancy.…”
Section: Introductionmentioning
confidence: 92%
“…16 In addition, the CXCL12/CXCR4 signaling pathway enhances progesterone-induced endothelial progenitor cell viability. 18 The above evidences suggest that CXCL12/CXCR4 axis plays an important role in embryonic development during the early pregnancy.…”
mentioning
confidence: 98%
“…Akt signaling pathway has a close relationship with cell viability and migration. Some studies showed that it was involved in progesterone-induced EPC viability ( 3 ). Notch signaling pathway is highly conserved, and plays a key role in neovascularization and angiogenesis process.…”
Section: Introductionmentioning
confidence: 99%